The Effect of Reinforcement on the Achievement of Islamic Religious Education Learning at Mts Anwarul Hidayah Ciputri - Ade Sofyan; Lita Arofatusolihah (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study is based on the fact that there is no concrete evidence explaining the extent of the relationship between the success of Islamic Religious Education learning at MTs Anwarul Hidayah Ciputri Menes, Pandeglang Regency, Banten. Therefore, the purpose of this study is to determine and analyze the relationship between the success of Islamic Religious Education learning and reinforcement. The purpose of this study was to determine the effect of reinforcement on the success of Islamic Religious Education learning. This study involved quantitative methods and the degree of influence between the two variables. This study involved 42 teachers and 42 eighth-grade students. Data were obtained through questionnaires and analyzed using simple linear regression tests, t-tests, and product-moment correlations. The results of the study indicate that the strong and positive category is included in the category with a correlation value of rxy = 0.93. This relationship is significant, according to the t-test, because tcount = 6.32 is greater than the table = 1.69. This coefficient of determination (Cd) of 90.25% indicates that reinforcement plays a significant role in learning success. While other factors influence 9.75%, the role of reinforcement is still evident. Therefore, it can be concluded that the more effective teachers are in providing both verbal and nonverbal reinforcement, the higher the students' learning success will be. Therefore, teachers must continue to develop warm, varied, and meaningful reinforcement methods to create a pleasant learning environment and shape students' characters in accordance with Islamic values